EFFECTIVENESS TEST OF ONION EXTRACT (Allium cepa L.) ON BACTERIA GROWTH Aeromonas hydrophila IN VITRO - Ulfa Wahyuni; Saptono Waspodo; Dewi Nur'aeni Setyowati (Journal of Fish Health, 2022)
Aeromonas hydrophila is a bacterium that causes MAS disease (Motile Aeromonas Septicemia), often found by cultivators. This study aimed to determine the effectiveness of onion extract (Allium cepa L.) in replacing chemical antibiotics and the correct dosage to inhibit the growth of Aeromonas hydrophila bacteria in vitro. The research method used was a Completely Randomized Design (CRD) with 7 treatments and 3 replications, P1 (Control-), P2 (Control+), P3 (10% onion extract), P4 (25% onion extract), P5 (50% onion extract), P6 (75% onion extract), P7 (100% onion extract). The results showed that 30 ml of onion extract obtained from 101.3 grams of onion powder had a yield value of 29.812%. Some secondary metabolite compounds in onion extract are flavonoids, alkaloids, saponins, tannins, steroids, and phenols, which function as antibacterial compounds. The diameter of the clear zone of 10% onion extract has a value of 26 mm and has a value that is not significantly different from the use of 50% chloramphenicol antibiotics with an inhibition zone diameter of 26.67 mm, treatment with onion extract with a concentration of 100% gives the same inhibition zone diameter. The highest is 34.17 mm.